(untitled) - The World Bank in Vietnam (WB) (Hà Nội, 2003)
The Coastal Wetlands Protection and Development Project will reestablish the coastal mangrove wetland ecosystems along the Mekong delta, and, protect its aquatic nurturing, for the development of the sustainable coastal protection it stands for. The components include: 1) provision of seedlings, civil works, and, equipment supply, for planting, rehabilitation, and, protection of mangrove forests, - barren, degraded, or, under new accretion land. Project management, and training, will focus on the protection of newly planted, or existing forests, and, improved forest conservation, and fish sanctuaries' management practices will be implemented; 2) institutional strengthening of the Vietnam Bank for Agriculture and Rural Development, and training, to improve creditability, and, grass roots organizations/farmer group demonstrations extension. Technology development and transfer, will improve farm productivity, decreasing farming risks; 3) social support, for the development, and implementation of commune action plans, and, establishment of communal grants, and social funds; 4) technical assistance and training for policy development assistance, to improve land, and water uses allocation, and, restructure selected enterprises; 5) resettlement plans, to assist affected groups, and, environmental assessment of bio-diversity, and socioeconomic impacts.
Keywords: Mangrove conservation,Sinh thái rừng ngập mặn,Coastal ecology,Sinh thái ven biển,Wetland ecology,Sinh thái ngập nước; Vietnam,Việt Nam,Vietnam,Việt Nam,Vietnam,Việt Nam